2023
DOI: 10.3390/ph16040487
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol-Loaded Nanocarriers and Their Therapeutic Applications

Abstract: Cannabidiol (CBD), one of the most promising constituents isolated from Cannabis sativa, exhibits diverse pharmacological actions. However, the applications of CBD are restricted mainly due to its poor oral bioavailability. Therefore, researchers are focusing on the development of novel strategies for the effective delivery of CBD with improved oral bioavailability. In this context, researchers have designed nanocarriers to overcome limitations associated with CBD. The CBD-loaded nanocarriers assist in improvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 111 publications
1
5
0
Order By: Relevance
“…Moreover, the observed enhanced neuron cell survival at low concentrations, coupled with lower toxicity compared to CBD alone, adds another layer of promise to the potential therapeutic application of CBD-LNP. These findings align with the broader understanding that nanoparticle formulations can enhance drug delivery efficiency and reduce toxicity [49,50]. The findings presented in this study not only demonstrate the successful preparation of CBD-LNP but also highlight its favorable physicochemical properties, stability, and reduced cytotoxicity, positioning it as a promising avenue for further exploration in the treatment of neurological disorders.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, the observed enhanced neuron cell survival at low concentrations, coupled with lower toxicity compared to CBD alone, adds another layer of promise to the potential therapeutic application of CBD-LNP. These findings align with the broader understanding that nanoparticle formulations can enhance drug delivery efficiency and reduce toxicity [49,50]. The findings presented in this study not only demonstrate the successful preparation of CBD-LNP but also highlight its favorable physicochemical properties, stability, and reduced cytotoxicity, positioning it as a promising avenue for further exploration in the treatment of neurological disorders.…”
Section: Discussionsupporting
confidence: 82%
“…The concentration-dependent opposite effects of CBD on neuronal survival suggest that its blood and brain concentration needs to be controlled. In connection with this, the CBD-loaded nanocarriers are currently being designed to overcome its poor oral bioavailability and improve the therapeutic efficacy of this compound [24,51,52]. Although clinical trials showed that CBD has an excellent safety profile and could be beneficial in the treatment of various neurological and neuropsychiatric conditions such as epilepsy, chronic pain, inflammation, anxiety, and neurodegenerative diseases, some undesired effects of this drug on hepatic drug metabolism and transport, fertility and in vitro cell viability were reported [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the inherent challenges associated with the bioavailability and degradation of CBD, our study has placed a significant emphasis on these aspects during the formulation of our SLNs. CBD, a compound with notable therapeutic potential, faces limitations in clinical applications due to its low bioavailability and susceptibility to degradation [31,32]. We have optimized the encapsulation efficiency (EE) and drug loading (DL) parameters of our SLNs through meticulous formulation strategies to address these challenges.…”
Section: Of 28mentioning
confidence: 99%